Exploring the Lived-Experience of business model innovation - Sangham, Mehul Anilrai (GSB: Faculty, 2016)
Due to increasingly complex and uncertain environments, businesses must deal with multiple competing and often opposing models, what we may call 'ontological relativity'. To deal with this, the practice of innovation management requires a new type of practical-epistemology. The best insight into these new types of knowledge is an exploration of lived experience of innovation management practitioners. This research then explores the phenomena involved in the practice of business model innovation in the context of two innovation projects. To achieve these goals, a phenomenological method is used to uncover fundamental aspects of the innovation process. The outcome of the inquiry is a set a set of phenomena that hope to contribute to the discourse around this emerging field of management knowledge.